Cerebellar stroke score and grading scale for the prediction of mortality and outcomes in ischemic cerebellar stroke - Won, Sae-Yeon; Melkonian, Ruzanna; Behmanesh, Bedjan; Bernstock, Joshua D.; Czabanka, Marcus; Dubinski, Daniel; Freiman, Thomas M.; Günther, Albrecht; Hellmuth, Kara; Hernandez-Duran, Silvia; Herrmann, Eva; Konczalla, Juergen; et al. (Stroke, 2023)
BACKGROUND: - - Several individual predictors for outcomes in patients with cerebellar stroke (CS) have been previously identified. There is, however, no established clinical score for CS. Therefore, the aim of this study was to develop simple and accurate grading scales for patients with CS in an effort to better estimate mortality and outcomes. - - METHODS: - - This multicentric retrospective study included 531 patients with ischemic CS presenting to 5 different academic neurosurgical and neurological departments throughout Germany between 2008 and 2021. Logistic regression analysis was performed to determine independent predictors related to 30-day mortality and unfavorable outcome (modified Rankin Scale score of 4-6). By weighing each parameter via calculation of regression coefficients, an ischemic CS-score and CS-grading scale (CS-GS) were developed and internally validated. - - RESULTS: - - Independent predictors for 30-day mortality were aged ≥70 years (odds ratio, 5.2), Glasgow Coma Scale score 3 to 4 at admission (odds ratio, 2.6), stroke volume ≥25 cm3 (odds ratio, 2.7), and involvement of the brain stem (odds ratio, 3.9). When integrating each parameter into the CS-score, age≥70 years and brain stem stroke were assigned 2 points, Glasgow Coma Scale score 3 to 4, and stroke volume≥25 cm3 1 point resulting in a score ranging from 0 to 6. CS-score of 0, 1, 2, 3, 4, 5, and 6 points resulted in 30-day mortality of 1%, 6%, 6%, 17%, 21%, 55%, and 67%, respectively. Independent predictors for 30-day unfavorable outcomes consisted of all components of the CS-score with an additional variable focused on comorbidities (CS-GS). Except for Glasgow Coma Scale score 3 to 4 at admission, which was assigned 3 points, all other parameters were assigned 1 point resulting in an overall score ranging from 0 to 7. CS-GS of 0, 1, 2, 3, 4, 5, 6, and 7 points resulted in 30-day unfavorable outcome of 1%, 17%, 33%, 40%, 50%, 80%, 77%, and 100%, respectively. Both 30-day mortality and unfavorable outcomes increased with increasing CS-score and CS-GS (P<0.001). - - CONCLUSIONS: - - The CS-score and CS-GS are simple and accurate grading scales for the prediction of 30-day mortality and unfavorable outcome in patients with CS. While the score systems proposed here may not directly impact treatment decisions, it may help discuss mortality and outcome with patients and caregivers.